Ortner's syndrome resulting from aortic pseudoaneurysm owing to intimal sarcoma of the aorta - Akio Shimoji, MD; Naoto Fukunaga, MD, PhD; Tatsuto Wakami, MD; Otohime Mori, MD; Kosuke Yoshizawa, MD; Nobushige Tamura, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
A 38-year-old man visited the otolaryngology department because of sudden onset of hoarseness a few days ago. A fiberoptic laryngoscopy revealed paralytic left vocal cord, indicating the left recurrent laryngeal nerve paralysis. Computed tomography angiography revealed a 44-mm aortic pseudoaneurysm with thrombus originating at the left subclavian artery. At total aortic arch replacement, an intimal defect was found at the origin of the left subclavian artery, where the pseudoaneurysm originated. A longitudinal ulcer-like lesion of intima was noticed. Pathology of the aortic wall revealed undifferentiated intimal sarcoma of the aorta. The aortic pseudoaneurysm developed owing to invasion of intimal sarcoma.